2000
DOI: 10.1115/1.1313528
|View full text |Cite
|
Sign up to set email alerts
|

Compressible Flow Through Solar Power Plant Chimneys

Abstract: Chimneys as tall as 1500 m may be important components of proposed solar chimney power plants. The exit air density will then be appreciably lower than the inlet density. The paper presents a one-dimensional compressible flow approach for the calculation of all the thermodynamic variables as dependent on chimney height, wall friction, additional losses, internal drag and area change. The method gives reasonable answers even over a single 1500 m step length used for illustration, but better accuracy is possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…(6) is, in effect, an explicit solution to the problem posed by Backstro¨m & Gannon [7] for u ðhÞ, and solved numerically. To see this, one can consider a constant diameter solar chimney, with parameters from [7] as follows: (6) and (7) give u ¼ 18:9 m=s and N e ¼ 205 MW which are in agreement with values obtained in [7].…”
Section: Updraft Powermentioning
confidence: 99%
See 1 more Smart Citation
“…(6) is, in effect, an explicit solution to the problem posed by Backstro¨m & Gannon [7] for u ðhÞ, and solved numerically. To see this, one can consider a constant diameter solar chimney, with parameters from [7] as follows: (6) and (7) give u ¼ 18:9 m=s and N e ¼ 205 MW which are in agreement with values obtained in [7].…”
Section: Updraft Powermentioning
confidence: 99%
“…Operation of the Solar Chimney has been successfully demonstrated, so the motive potential of an updraft can in fact be used to perform useful work. The motive potential increases with both height of the chimney, and with the temperature rise in the greenhouse [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…30). proposed 1500 m high solar chimney with an inner diameter of 160 m that had been carried out by Backstrom and Gannon [135]. They showed that with an increase in the chimney height, the temperature of the outflow decreased due to more thermal energy being converted to gravitational potential energy [136].…”
Section: Analytical and Simulation Studiesmentioning
confidence: 99%
“…The performance of solar chimney plants has been investigated by several researchers [1][2][3][4][5]. Among others, Serag-Eldin [6] has shown that, for a given collector area, the performance increases rapidly with increase of height of stack.…”
Section: Conventional Solar-chimney Plantmentioning
confidence: 99%